Intraligamentary Pregnancy- A Rare Obstetric Event - Khair, Asma Binte; Rahman, Mahmuda; Afroz, Rumana (Medicine Today, 2023)
Introduction: Intraligamentary pregnancy is a rare form of ectopic pregnancy, where the gestation grows within the leaves of the broad ligament. Clinical presentation, diagnosis and outcome are highly variable. Case report: Here, we report a case of a 30 years old lady (P2G7), presented at her 13+ weeks of pregnancy with acute abdomen and severe anaemia. USG revealed extrauterine alive pregnancy with huge peritoneal collection. Emergency laparotomy was performed and final diagnosis was made as ruptured intraligamentary pregnancy. Right sided salpingooophorectomy was done. Our main challenge was to control bleeding and to maintain haemostasis at the placental implantation site. Conclusion: Although, definite preoperative diagnosis based on clinical sign symptoms and sonographic evaluation is elusive, proper resuscitation and surgical expertise can save a mother’s life. Role of MRI and Laparoscopy in selected cases should be in consideration. Medicine Today 2023 Vol.35(1): 70-72